(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Many urban kampungs in Yogyakarta have undergone significant transformation into tourism-oriented destinations, including the neighborhood of Prawirotaman. This transformation has contributed to the reduction of children’s play spaces and has limited opportunities for outdoor play experiences compared to those available to children living in rural environments. Consequently, children are required to continuously negotiate and adapt to the spatial and social changes occurring within their neighborhood context. Accordingly, this study seeks to examine the relationship between play territoriality and the spatial experiences that shape children’s behavioral responses, while simultaneously addressing existing research gaps concerning children’s territorial adaptation behavior. Data collection was conducted through snapshot observations to document children’s play activities and movement patterns, including gestures, conversations, spatial settings, and the objects involved in play activities. These observations were further supported by drawings, narratives, and mapping techniques. The study employed a behavioral approach combined with content analysis methods. The findings reveal that children living within kampung environments adapt to ongoing neighborhood transformation through forms of territorial leeway that enable play activities to persist. Furthermore, children’s spatial experiences significantly influence their adaptive behavior, their perceptions of transitional spaces, and the extent of their play territories. This study contributes to the enrichment of architectural behavioral theory and provides a foundational framework for the development of child-friendly residential settlements.